PARTICIPANTS SATISFACTION CHARACTER EDUCATION AND TRAINING DEVELOPMENT CADET POST PRALA - GIRI KURNIA WIDYASARI; DYAN APRIYANI (IKIP Siliwangi Bandung, 2018)
The purpose of the study to know the level of satisfaction of the participants of Development Training Character Cadet Post Prala Polytechnic Science Semarang on the implementation of training and education and Training Center of Human Resource Character Building Transportation. The items of satisfaction that become the assessment are a) Teachers, b) Materials and Methods, c) Implementation which includes; organizers, facilities and infrastructure and food. The population of the research is post-skilled polytechnic skala polytechnic of Semarang. Samples of Research Group 1 Cadet Post Prala PIP Semarang. The research data was obtained from the questionnaire given after the end of the training. This research is a descriptive research. The results of the data analysis were obtained using a scale rating consisting of: 1 = unsatisfactory, 2 = less satisfactory, 3 = satisfactory, 4 = satisfactory, 5 = very satisfactory. The calculation method gets the average yield of the total value of IKP divided by the number of samples. The conclusion of the research: 1) Satisfaction of the training participants on the teachers got very satisfactory value. This is evident from the mean for faculty facilitators = 4.08 and TNI trainers = 4.12. 2) Materials and methods, got very satisfactory value. Participants assessed materials and methods for facilitator material = 4.08 and TNI trainers = 4.08. 3) Operation gets satisfactory score with score 3,42. of the training participants.